2016
DOI: 10.1371/journal.pone.0153917
|View full text |Cite
|
Sign up to set email alerts
|

Assessing Specific Cognitive Deficits Associated with Dementia in Older Adults with Down Syndrome: Use and Validity of the Arizona Cognitive Test Battery (ACTB)

Abstract: BackgroundDown syndrome is associated with specific cognitive deficits. Alongside this, older adults with Down syndrome are a high risk group for dementia. The Arizona Cognitive Test Battery (ACTB), a cognitive assessment battery specifically developed for use with individuals with Down syndrome, has been proposed for use as outcome measures for clinical trials in this population. It has not been validated in older adults with Down syndrome. This study aims to assess the use and validity of the ACTB in older a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
47
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 34 publications
(50 citation statements)
references
References 44 publications
3
47
0
Order By: Relevance
“…Fully understanding the time course of dementia development in DS is essential for better detection and monitoring of cognitive decline, to detect reliable biomarkers for the progression of decline, and for the development of clinical trials. Previous studies have also demonstrated poorer performance associated with aging, cognitive decline, and dementia in adults with DS for various tasks within our battery [23] , [28] , [29] , [30] , [31] , [32] . Study results have however differed regarding the sequence of cognitive changes.…”
Section: Discussionsupporting
confidence: 52%
See 1 more Smart Citation
“…Fully understanding the time course of dementia development in DS is essential for better detection and monitoring of cognitive decline, to detect reliable biomarkers for the progression of decline, and for the development of clinical trials. Previous studies have also demonstrated poorer performance associated with aging, cognitive decline, and dementia in adults with DS for various tasks within our battery [23] , [28] , [29] , [30] , [31] , [32] . Study results have however differed regarding the sequence of cognitive changes.…”
Section: Discussionsupporting
confidence: 52%
“…Informant measures are important for adults who cannot engage in cognitive assessments, who have vision or hearing difficulties, or who are at floor on cognitive tests. Our battery has previously been validated and adapted for use in older adults with DS, including those with little verbal ability [8] , [23] , and focuses on abilities related to memory, executive function, and motor coordination, as these are often impaired in DS [19] and further impaired by dementia [23] .…”
Section: Methodsmentioning
confidence: 99%
“…In addition, participants completed a modified version of the Tower of London executive function test (Krikorian, Bartok, & Gay, 1994) adapted for people with intellectual disability by Ball and colleagues (Ball, Holland, Treppner, Watson, & Huppert, 2008), scored out of 12. IQ was measured using the raw IQ scores from the Kaufmann Brief Intelligence Test, 2nd edition (KBIT-II; Kaufman & Kaufman, 2004), since using standard scores would result in many participants scoring at floor (Sinai, Hassiotis, Rantell, & Strydom, 2016).…”
Section: Neuropsychological Assessmentmentioning
confidence: 99%
“…However, object memory, semantic verbal fluency, the cued recall task, Tower of London, the CANTAB paired associate learning and simple reaction time tasks and visuomotor precision tasks are between the suitable cognitive test for distinguishing between those with and without dementia and tracking dementia-related decline. 8,[29][30][31][32] Validation of the NIH Toolbox (HealthMeasures, Evanston, Illinois, USA) Cognitive Battery for intellectual disability found that Flanker inhibition/ attention tasks, picture vocabulary, oral reading, and picture sequence memory tasks were accessible to those with intellectual disability.…”
Section: Clinical Symptomsmentioning
confidence: 99%